2021
DOI: 10.1177/0271678x211003497
|View full text |Cite
|
Sign up to set email alerts
|

Telmisartan prevents high-fat diet-induced neurovascular impairments and reduces anxiety-like behavior

Abstract: Angiotensin II receptor blockers (telmisartan) prevent rodents from diet-induced obesity and improve their metabolic status. Hyperglycemia and obesity are associated with reduced cerebral blood flow and neurovascular uncoupling which may lead to behavioral deficits. We wanted to know whether a treatment with telmisartan prevents these changes in obesity. We put young mice on high-fat diet and simultaneously treated them with telmisartan. At the end of treatment, we performed laser speckle imaging and magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 61 publications
(112 reference statements)
5
20
2
Order By: Relevance
“…On the other hand, object recognition tasks still depicted impaired memory performance in the HFHSD-fed mice. By analyzing free open-field exploration, we further found HFHSD-induced impairments in novel environment exploration and increased anxiety-like behavior (Prut & Belzung, 2003), as was also reported for mice exposed to HFD (Huber et al, 2021), and in line with a proposed obesity associated depression (e.g. Vagena et al, 2019).…”
Section: Metabolic Syndrome and Brain Functionsupporting
confidence: 84%
See 1 more Smart Citation
“…On the other hand, object recognition tasks still depicted impaired memory performance in the HFHSD-fed mice. By analyzing free open-field exploration, we further found HFHSD-induced impairments in novel environment exploration and increased anxiety-like behavior (Prut & Belzung, 2003), as was also reported for mice exposed to HFD (Huber et al, 2021), and in line with a proposed obesity associated depression (e.g. Vagena et al, 2019).…”
Section: Metabolic Syndrome and Brain Functionsupporting
confidence: 84%
“…Therefore, one might speculate that increased NAAG levels together with an increased A2A receptor tone in astrocytes causes a dysfunctional regulation of astrocyte-mediated neurovascular coupling. In support of this, neurovascular dysfunction has been reported after 16, but not 8 weeks, of HFD feeding (Huber et al, 2021).…”
Section: Alterations In Brain Metabolismmentioning
confidence: 64%
“…On the other hand, object recognition tasks still depicted impaired memory performance in the HFHSD-fed mice. By analyzing free open-field exploration, we further found HFHSD-induced impairments in novel environment exploration and increased anxiety-like behavior [ 25 ], as was also reported for mice exposed to HFD [ 28 ], and in line with a proposed obesity associated depression [ 29 ].…”
Section: Discussionmentioning
confidence: 67%
“…Thus, AngII receptor (type 1) blockers (ARBs) such as telmisartan (TEL) and losartan (LOS) are well-established in the treatment of hypertension and heart failure, particularly with regard to their cardiometabolic benefits ( Michel et al, 2016 ). Beyond these beneficial actions, ARBs have been demonstrated to preventively and curatively lower obesity in rodents ( Muller-Fielitz et al, 2011 ; Miesel et al, 2012 ; Muller-Fielitz et al, 2012 ; Muller-Fielitz et al, 2014 ; Muller-Fielitz et al, 2015 ; Schuchard et al, 2015 ; Schuster et al, 2018 ; Winkler et al, 2018 ; Gustaityte et al, 2019 ; Rawish et al, 2020 ; Huber et al, 2021 ) and humans ( Kintscher et al, 2007 ). The anti-obese potency of ARBs occurs mainly after high dosages and is independent of their ability to reduce blood pressure ( Muller-Fielitz et al, 2011 ; Muller-Fielitz et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…ARB-induced weight loss correlates with a reduction of energy intake, fat mass, and size of adipocytes ( Miesel et al, 2012 ; Muller-Fielitz et al, 2012 ). Although the underlying mechanism remains a matter of debate, it was found that leptin-related ( Muller-Fielitz et al, 2011 ; Muller-Fielitz et al, 2012 ; Schuster et al, 2018 ) and other brain-related mechanisms ( Winkler et al, 2016 ; Rawish et al, 2020 ; Huber et al, 2021 ) are involved in ARB-induced regulation of energy homeostasis. Addressing brain-related mechanisms, we have repeatedly shown that obesity-induced leptin resistance is normalized by TEL, as leptin can once again cross the blood‒brain barrier ( Muller-Fielitz et al, 2011 ; Muller-Fielitz et al, 2012 ; Schuster et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%